2021
DOI: 10.1590/1413-81232021269.2.28252019
|View full text |Cite
|
Sign up to set email alerts
|

Baixa ingestão de fibras alimentares em idosos: estudo de base populacional ISACAMP 2014/2015

Abstract: Resumo O objetivo deste artigo é avaliar a prevalência de inadequação do consumo de fibras alimentares e seus fatores associados em idosos. Estudo transversal de base populacional que avaliou participantes do Inquérito de Saúde do Município de Campinas (ISACAMP) em 2014/2015, com 1.074 idosos (≥60 anos). O consumo de fibras na dieta foi obtido utilizando um recordatório de 24h, e foi estimada a prevalência de inadequação de fibras de acordo com o ponto de corte do Institute of Medicine (30 g/dia para homens e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
(48 reference statements)
0
3
0
1
Order By: Relevance
“…In addition, aging anorexia may be influenced by lower food palatability. This may motivate an overall reduction in food interest and a choice of less varied diets from a nutritional point of view, with an increase in more palatable foods with higher sugar amount 33,34 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, aging anorexia may be influenced by lower food palatability. This may motivate an overall reduction in food interest and a choice of less varied diets from a nutritional point of view, with an increase in more palatable foods with higher sugar amount 33,34 .…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy might be attributable to the different methodologies used to assess dietary habits. Additionally, a Brazilian study reported a low daily protein intake of 65.12 g/day among 47 women [ 82 ] and the Health Survey of the City of Campinas (ISACAMP) highlighted a high prevalence of inadequate dietary fiber intake (86.6%) [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…Idosos podem ter menor apetite fisiológico, consumir menor quantidade de comida por refeição e de maneira lenta, influenciando na saciedade precoce e na diminuição do aporte energético diário, ocasionando o balanço energético negativo, e, por consequência, a perda de peso corporal. Além disso, a anorexia do envelhecimento pode ser influenciada por uma menor palatabilidade dos alimentos, o que pode motivar uma redução global no interesse alimentar e na escolha de uma dieta menos variada do ponto de vista nutricional, com o aumento de alimentos mais palatáveis como maior quantidade de açúcares 33,34 .…”
Section: Discussionunclassified